Diffusion tensor imaging of fetal brain: principles, potential and limitations of promising technique. (2nd October 2022) - Corroenne, R.; Arthuis, C.; Kasprian, G.; Mahallati, H.; Ville, Y.; Millischer Bellaiche, A.‐E.; Henry, C.; Grevent, D.; Salomon, L. J.
Abstract: Human brain development is a complex process that begins in the third week of gestation. During early development, the fetal brain undergoes dynamic morphological changes. These changes result from events such as neurogenesis, neuronal migration, synapse formation, axonal growth and myelination. Disruption of any of these processes is thought to be responsible for a wide array of different pathologies. Recent advances in magnetic resonance imaging, especially diffusion‐weighted imaging and diffusion tensor imaging (DTI), have enabled characterization and evaluation of brain development in utero . In this review, aimed at practitioners involved in fetal medicine and high‐risk pregnancies, we provide a comprehensive overview of fetal DTI studies focusing on characterization of early normal brain development as well as evaluation of brain pathology in utero . We also discuss the reliability and limitations of fetal brain DTI. © 2022 International Society of Ultrasound in Obstetrics and Gynecology.